2020
DOI: 10.1101/2020.09.23.290593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tuning TPO-R signaling to influence hematopoietic stem cell differentiation and inhibit essential thrombocythemia

Abstract: Thrombopoietin (TPO) and the TPO-receptor (TPO-R, or c-MPL)) are essential for hematopoietic stem cell (HSC) maintenance and megakaryocyte differentiation. Agents that can modulate TPO-R signaling are highly desirable, both experimentally and clinically. We have developed a series of surrogate protein-ligands for TPO-R, in the form of diabodies, that homodimerize the TPO-R on the cell surface in different geometries, in effect tuning downstream signaling responses. These surrogate ligands exhibit diverse pharm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…STAT5 signaling has been shown to be critical for stemness and self-renewal (65-70), whereas STAT1 signaling has been implicated in monocytic differentiation and macrophage maturation (50,51). Importantly, disrupting the balance between STAT5, STAT1, and STAT3 signaling can alter differentiation kinetics and cell fate in normal hematopoiesis (6,71) and in hematologic diseases (72). We postulate that different receptor assemblies alter the balance between STAT5 and STAT1 signaling.…”
Section: Discussionmentioning
confidence: 95%
“…STAT5 signaling has been shown to be critical for stemness and self-renewal (65-70), whereas STAT1 signaling has been implicated in monocytic differentiation and macrophage maturation (50,51). Importantly, disrupting the balance between STAT5, STAT1, and STAT3 signaling can alter differentiation kinetics and cell fate in normal hematopoiesis (6,71) and in hematologic diseases (72). We postulate that different receptor assemblies alter the balance between STAT5 and STAT1 signaling.…”
Section: Discussionmentioning
confidence: 95%
“…We propose that this structural difference affects the efficacies of the two lectins. A recent study demonstrated that dimeric antibodies that bridge and dimerize MPL by binding various sites near the canonical ligand-binding domain of MPL activated the receptor in distinctive ways, which realized agonist-based decoupling of HSC self-renewal and differentiation (22). Because no structural information on the 'active' receptor complex for MPL was known, the mechanistic basis of this phenomenon was elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these new methods will provide a better understanding of the molecular mechanism of MPL activation by TPO and open avenues to the development of novel strategies for the modulation of the pathway. In an important first step, Cui and coworkers have recently discovered and characterized anti-MPL diabodies with differential effects on signaling output[ 101 ], which appear to separate the dual roles of MPL signaling; HSC self-renewal and megakaryocyte differentiation. As the development of highly specific synthetic cytokines gathers pace[ 102 ] it is tempting to speculate that additional modalities targeting the MPL ECD to alter signaling output could also be achieved.…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%